Strategic Leadership as Determinant of Strategic Change: A Theoretical Review and Propositions - Ayi Ahadiat (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2009)
The strategic change is an issue that closely related to strategic leadership. As this paper elaborates how strategic leadership determines the strategic change, the elaboration of both concept and their relationship are presented through propositions that are developed from the modified Hambrick’s model. Strategic leadership that causes strategic change in terms of strategic process and content within environmental and organizational context will lead to organizational performance as an ultimate outcome.